Prinsip Notaris Dalam Pengenalan Pelaku Tindak Pidana Pencucian Uang - Kartina Pakpahan; Maggie Maggie; Christian Agung Prawito; Wico Dwi Pratama (jurnal.unprimdn.ac.id, 2020)
Prinsip Notaris Dalam Pengenalan Pelaku Tindak Pidana Pencucian Uang Kartina Pakpahan, Maggie, Christian Agung Prawito, Wico Dwi Pratama Abstract Fakultas Hukum Universitas Prima Indonesia Jalan Sekip Simpang Sikambing, Medan, Sumatera Utara maggielie52@gmail.com Written statutory regulation has given a role to the Notary regarding to eradication of the criminal offence of money laundering. Basically the duties and obligations of a Notary are to make a deed in accordance with the statement made by the parties before the Notary based on what is seen and heard by the Notary. The Notary's capability in implementing its duty related to the truth statements of the parties and testimony of the truth of what is seen and heard by the Notary, it is only confined to the formal truth and not the material truth. Based on its capability, it is difficult for the Notary to seek for the material truths that can prove the existence of a criminal offense of money laundering. The Notary’s role in identifying the perpetrator of money laundry by the Notary as regulated in statutory regulation is still ineffective or not in line with expectations because the regulation has not gone well and cannot yet become an accurate indicator in identifying a crime at the early stage of the perpetrators of money laundering by the Notary. In the future, the Notary in carrying out its duties require an accurate indicator to be able to identify the perpetrators of money laundering crime optimally based on statutory regulations. Intisari Peraturan perundang-undangan secara tertulis telah memberikan peranan terhadap Notaris dalam pemberantasan tindak pidana pencucian uang. Pada dasarnya tugas dan kewajiban Notaris adalah membuat akta sesuai dengan pernyataaan para penghadap dihadapan Notaris atau membuat akta sesuai dengan yang dilihat dan didengar oleh Notaris. Kemampuan Notaris dalam menjalankan tugasnya atas kebenaran pernyataan para penghadap dan kebenaran apa yang dilihat serta didengar oleh Notaris tersebut hanya sampai kebenaran formil tidak sampai kebenaran materiil. Berdasarkan kemampuannya, sulit bagi Notaris untuk mencari kebenaran materiil yang membuktikan adanya tindak pidana pencucian uang. Peran notaris dalam mengenali pelaku pencucian uang oleh Notaris yang diatur dalam peraturan perundang-undangan masih belum efektif atau tidak sesuai dengan harapan karena peraturan tersebut belum berjalan dengan baik dan belum dapat menjadi indikator yang akurat dalam mengenali pelaku kejahatan pencucian uang oleh Notaris. Kedepannya, Notaris dalam menjalankan tugasnya membutuhkan suatu indikator yang akurat untuk dapat mengenali pelaku kejahatan pencucian uang secara optimal berdasarkan peraturan perundang-undangan..